Distribution of serotype-specific genotypes of Aggregatibacter actinomycetemcomitns in Brazilian patients with Down syndrome with different periodontal conditions - Gaetti-Jardim Júnior, Elerson [UNESP] (2013)
This study evaluated the occurrence of highly or minimally leukotoxic strains of Aggregatibacter actinomycetemcomitans (Aa) from patients with Down syndrome and the distribution of the different serotype-specific genotypes of this microorganism. Sixty-seven patients with Down syndrome were subjected to dental, periodontal and radiographic evaluations. Samples of subgingival biofilm were collected and plated onto TSBV agar and characteristic colonies of A. actinomycetemcomitans were identified by biochemical methods. The occurrence of this bacterium was also evaluated directly in the clinical specimens by PCR. The presence of 530 bp deletion in the promoter region was also determined by PCR in order to evaluate distribution of highly or minimally leukotoxic strains. A. actinomycetemcomitans was detected in 11.1% by culture and 22.2% by PCR from periodontally healthy subjects, 100% of the patients with Down syndrome with aggressive periodontitis, 50% and 75% of patients with chronic periodontitis by culture and PCR respectively. Only two patients with aggressive periodontitis were colonized by highly leukotoxic Aa. Serotype-specific genotypes a and c were the most prevalent. The results suggest the role of peculiar characteristics of Aa and patients with Down syndrome in the development of periodontitis and the influence of peculiar characteristics of the population in this process.